TEACHING ENGLISH TO THE TEACHERS OF SPECIAL NEEDS STUDENTS AT PANTI SOSIAL BINA GRAHITA BELAIAN KASIH - Murniati, Murniati; Junita, Junita (Jurnal Pengabdian dan Kewirausahaan, 2021)
ABSTRACT                 All teaches need to improve themselves in terms of content and the teaching methods. Unfortunately, there has been a little enrichment delivered due to the pandemic which still occurs in 2021. This community service, therefore, is delivered to the teachers of special needs students at Panti Sosial Bina Grahita Belaian Kasih since to enrich their English knowledge as well as teaching skills for the special needs students. Needs analysis was administered to find (1) the Present Situation Analysis of the teachers, (2) the Learning Situation Analysis which cover the delivery of the community services, and (3) the Target Situation Analysis which cover the topics delivered during the community services. It was found out that there were twelve (12) teachers who would join this enrichment English class. Since bot all of them were English teachers, the English content should also be discussed during the community services. Next, the community services delivered five times through google meet and zoom meeting, on Wednesdays and Fridays in March 2021. The topics delivered are (1) learning styles and teaching methods for special needs students, (2) the English alphabets, (3) shapes and colors, (4) emotions, and (5) action verbs in English. The community services ran well. For better results, more meetings are needed to enrich the teachers’ teaching skills as well as their English abilities and knowledge, especially which are related to the special needs students.